Facile preparation of antibacterial hydrogel with multi-functions based on carboxymethyl chitosan and oligomeric procyanidin. Issue 32 (21st July 2022) - He, Yuanmeng; Guo, Shen; Chang, Rong; Zhang, Dan; Ren, Yikun; Guan, Fangxia; Yao, Minghao
Abstract : An injectable, self-healing, adhesive, and antibacterial CMCS/OPC hydrogel based on carboxymethyl chitosan (CMCS) and oligomeric procyanidin (OPC) was fabricated and characterized. Abstract : Hydrogel-based antibacterial materials with multi-functions are of great significance for healthcare. Herein, a facile and one-step method was developed to fabricate an injectable hydrogel (named CMCS/OPC hydrogel) based on carboxymethyl chitosan (CMCS) and oligomeric procyanidin (OPC). In this hydrogel system, OPC serves as the dynamic crosslinker to bridge CMCS macromolecules mainly through dynamical hydrogen bonds, which endows this hydrogel with excellent injectable, self-healing, and adhesive abilities. In addition, due to the inherent antibacterial properties of CMCS and OPC, this hydrogel shows excellent antibacterial activity. Therefore, the well-designed CMCS/OPC hydrogel has great prospects as an antibacterial material in the biomedical field.